Quaternary Deposit Response to Earthquakes in Pemalang City Based on Peak Ground Acceleration, Earthquake Intensity, and Microtremor Method - Urip Nurwijayanto Prabowo; Sehah Sehah; Akmal Ferdiyan; Sismanto Sismanto (Indonesian Journal on Geoscience, 2023)
The northern part of Pemalang City consists of Quaternary deposits, having the potential for earthquake amplification effect. This amplification effect amplifies the ground shaking because of an earthquake (the local site effect) that has the potential to cause damage. This study investigated the amplification factor from the HVSR curve of microtremor measurements due to soil response based on ground shear strain, the risk level of the earthquake based on peak ground acceleration (PGA), and earthquake intensity. The microtremor data from five locations in Pemalang were used to calculate the amplification factor and predominant frequency. The damaging earthquake parameters around Java during 2010-2020 were used to calculate the PGA. The microtremor data were processed using the HVSR method, and PGA was calculated using the Kanai equation. The HVSR result shows that Pemalang has an amplification factor ranging from 6.23 to 19.59 and ground shear strain varying between 0.86 x 10-4 and 6.67 x 10-4, which shows that Pemalang only experiences the vibration when an earthquake occurs. The PGA results using the Kanai equation (19.71-54.56 gal) were included in the low vulnerability category, and MMI earthquake intensity (3.08-4.70) was included in the felt earthquake category (II SIG BMKG scale). Therefore, the amplification factor from the HVSR curve of microtremor measurement, ranging from 6.23 to 19.59, showed low soil response and low-risk vulnerability based on the damaging earthquake parameter around Java during 2010-2020. Keywords: peak ground acceleration, amplification, microtremor, PGA